LINE Webtoon as Digital Literacy Model - Rauf, Ramis; Duwila, Ety (International Journal of Transdisciplinary Knowledge, 2022)
This study aims to reveal LINE Webtoon as the development of literacy in education, language, literature, and culture, which is a representation of the positive side of social media usage in this digital era. LINE Webtoon is created by Daum and has been published in as many as 434 variants of comic series from its inception in 2003 until today. This paper will explore more about the LINE Webtoon as the virtual web is seen as the latest model of digital literacy in the process to enjoy literary works through social media.